People in the news - Brownstone, David M.; Franck, Irene M. (New York Simon & Schuster Macmillan, 1996)
Presents clear, up-to-date biographical information on a wide selection of the most newsworthy people in the world.
Keywords: Celebrities -- Biography -- Juvenile literature; Biography -- 20th century -- Juvenile literature; Biography; Celebrities